Marine Streptomyces sp. Isolated From the Brazilian Endemic Tunicate Euherdmania sp. Produces Dihydroeponemycin and Analogs With Potent Antiglioma Activity - Furtado, Luciana C.; Bauermeister, Anelize; de Felicio, Rafael; Ortega, Raquel; Pinto, Francisco das Chagas L.; Machado-Neto, João Agostinho; Trivella, Daniela B. B.; Pessoa, Otilia D. L.; Wilke, Diego V.; Lopes, Norberto P.; Jimenez, Paula C.; Costa-Lotufo, Leticia V. (Frontiers in Marine Science, 2021)
Marine natural products have emerged as an important source for drug development, notably in the field of anticancer therapy. Still, the limited effectiveness of current therapies for central nervous system tumors indicates the need to identify new therapeutic targets and also novel pharmacological agents. In this context, proteasome inhibitors are appearing as a promising new treatment for these diseases. Herein, cytotoxic extracts produced by four marine bacteria recovered from the Brazilian endemic ascidian Euherdmania sp. were screened to evaluate their potential as proteasome inhibitors. The extract from marine Streptomyces sp. BRA-346 was selected for further investigation due to the potent proteasome inhibitory activity it displayed. Bioassay-guided fractionation led to an enriched fraction (proteasome inhibition IC50 = 45 ng/mL), in which the presence of dihydroeponemycin (DHE), known for its proteasome inhibitory effect, and related compounds were annotated by mass spectrometry and further confirmed by comparison with DHE standard. Both DHE and the epoxyketone-containing fraction were evaluated in glioma cell lines, displaying high cytotoxicity in HOG and T98G cells (GI50 of 1.6 and 1.7 ng/mL for DHE, and 17.6 and 28.2 ng/mL for the BRA-346 fraction, respectively). Additional studies showed that the epoxyketone-containing fraction (at GI50 levels) led to an accumulation of ubiquitinated proteins and up-regulation of genes related to ER-stress response, suggesting treated cells are under proteasome inhibition. DHE induced similar effects in treated cells but at concentrations 25 times its GI50, suggesting that the other epoxyketone compounds in the bacteria extract derived fraction may contribute to enhance proteasome inhibition and further cellular effects in glioma cells. These findings revealed the molecular pathways modulated by this class of compounds in glioma cells and, moreover, reinforced the potential of this marine bacteria in producing a cocktail of structurally-related compounds that affect the viability of glioma cells.